CAEP 2016 Academic Symposium: A Writer's Guide to Key Steps in Producing Quality Education Scholarship. (15th May 2017) - Chan, Teresa M.; Thoma, Brent; Hall, Andrew Koch; Murnaghan, Aleisha; Ting, Daniel K.; Hagel, Carly; Weersink, Kristen; Camorlinga, Paola; McEwen, Jill; Bhanji, Farhan; Sherbino, Jonathan
Abstract: A key skill for successful clinician educators is the effective dissemination of scholarly innovations and research. Although there are many ways to disseminate scholarship, the most accepted and rewarded form of educational scholarship is publication in peer-reviewed journals. This paper provides direction for emergency medicine (EM) educators interested in publishing their scholarship via traditional peer-reviewed avenues. It builds upon four literature reviews that aggregated recommendations for writing and publishing high-quality quantitative and qualitative research, innovations, and reviews. Based on the findings from these literature reviews, the recommendations were prioritized for importance and relevance to novice clinician educators by a broad community of medical educators. The top items from the expert vetting process were presented to the 2016 Canadian Association of Emergency Physicians (CAEP) Academic Symposium Consensus Conference on Education Scholarship. This community of EM educators identified the highest yield recommendations for junior medical education scholars. This manuscript elaborates upon the top recommendations identified through this consensus-building process. Résumé: : L'une des principales clés du succès parmi les médecins cliniciens enseignants est la diffusion efficace des travaux scientifiques touchant la recherche ou l'innovation. Certes, il existe de nombreux moyens de diffuser des travaux scientifiques, mais la forme la plus courante et la plus prestigieuse est la publication de travaux de recherche en éducation dans des revues à comité de lecture. Les auteurs offrent, dans l'article, une voie à suivre aux médecins enseignants en médecine d'urgence (MU), désireux de publier leurs travaux scientifiques par la voie classique des articles évalués par les pairs. Le contenu repose sur quatre examens de la documentation qui ont permis de dégager des recommandations sur la rédaction et la publication de travaux de qualité concernant la recherche quantitative ou qualitative, les rapports sur l'innovation ou les revues systématiques. Les recommandations, tirées des examens de la documentation, ont été classées par ordre de priorité en fonction de l'importance et de la pertinence pour les nouveaux cliniciens enseignants, par un large éventail de médecins enseignants. Les principaux éléments extraits de cet examen détaillé, réalisé par des experts, ont été présentés durant la conférence consensuelle sur les travaux scientifiques en enseignement, tenue dans le cadre du Symposium sur les affaires universitaires de l'ACMU de 2016. La communauté de cliniciens enseignants en MU a dégagé les recommandations qui leur semblaient les plus utiles aux jeunes chercheurs en enseignement de la médecine. L'article fait donc état des principales recommandations relevées tout le long de ce processus consensuel d'édification.